Quality management maturity: Its application and evaluation in Chinese private equipment manufacturing enterprises - Zhu Guojie (2022)
Although China’s private equipment manufacturing enterprises have made significant progress, quality problems still occur because of the weak quality foundation. Therefore, it is necessary to scientifically evaluate the quality management of equipment manufacturing enterprises, identify the deficiencies and defects of quality management, and provide systematic and targeted countermeasures and suggestions. The thesis conducted text analysis on the quality award self-assessment materials of three companies and constructed an evaluation model for private equipment manufacturing enterprises including four sub-systems (management process, support process, customeroriented process and result) through three-level coding. Meanwhile, in order to empirically test the quality management maturity evaluation model of private equipment enterprises and explore the relationships between the sub-systems, the thesis selected 6 private equipment enterprises located in Guizhou province as the pre-survey objects and selected 80 private manufacturing enterprises located in Beijing, Zhejiang province, Guizhou province, Hunan province, and Sichuan province as the formal survey objects to carry out hypothesis test. Moreover, the thesis developed a maturity evaluation scale. Applying the scale to the case GXTF company, the thesis proposed improvement strategies for GXTF company. In theory, the thesis enriched the research on the quality management of private equipment manufacturing enterprises. In practice, the thesis provided reference for maturity evaluation, and provided an updated version for GJB9001C quality management accreditation institutions.